Intrauterine Transfer of Polyunsaturated Fatty Acids in Mother–Infant Dyads as Analyzed at Time of Delivery - Woodard, Vanessa (Nutrients, 2021)
Polyunsaturated fatty acids (PUFAs) are essential for fetal development, and intrauterine transfer is the only supply of PUFAs to the fetus. The prevailing theory of gestational nutrient transfer is that certain nutrients (including PUFAs) may have prioritized transport across the placenta. Numerous studies have identified correlations between maternal and infant fatty acid concentrations; however, little is known about what role maternal PUFA status may play in differential intrauterine nutrient transfer. Twenty mother–infant dyads were enrolled at delivery for collection of maternal and umbilical cord blood, and placental tissue samples. Plasma concentrations of PUFAs were assessed using gas chromatography (GC-FID). Intrauterine transfer percentages for each fatty acid were calculated as follows: ((cord blood fatty acid level/maternal blood fatty acid level) × 100). Kruskal–Wallis tests were used to compare transfer percentages between maternal fatty acid tertile groups. A p-value < 0.05 was considered significant. There were statistically significant differences in intrauterine transfer percentages of arachidonic acid (AA) (64% vs. 65% vs. 45%, p = 0.02), eicosapentaenoic acid (EPA) (41% vs. 19% vs. 17%, p = 0.03), and total fatty acids (TFA) (27% vs. 26% vs. 20%, p = 0.05) between maternal plasma fatty acid tertiles. Intrauterine transfer percentages of AA, EPA, and TFA were highest in the lowest tertile of respective maternal fatty acid concentration. These findings may indicate that fatty acid transfer to the fetus is prioritized during gestation even during periods of maternal nutritional inadequacy.